2014
DOI: 10.1007/s10396-014-0525-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the sonographic fat pad sign for primary screening of pediatric elbow fractures: a preliminary study

Abstract: The sonographic FPS could serve as a useful screening tool in primary evaluation of pediatric elbow injuries. If a fracture is unlikely after clinical and US evaluation, additional radiographs are dispensable, thereby potentially minimizing the radiation burden in childhood and reducing the length of stay in the Emergency Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…As limitations, the authors mentioned that they had only one specialist that used ultrasound, suggesting that the diagnosis could be subjective. In contrast to other anatomical regions, the complete sonographic exam of the elbow is more sophisticated and requires a well-prepared specialist [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As limitations, the authors mentioned that they had only one specialist that used ultrasound, suggesting that the diagnosis could be subjective. In contrast to other anatomical regions, the complete sonographic exam of the elbow is more sophisticated and requires a well-prepared specialist [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study published by K. Eckert, O. Ackermann, N. Janssen et al in 2013, in which the accuracy of the US was followed in the diagnosis of posterior fat pad sign, as a predictor for the elbow fractures on pediatric patients, the authors found the following results: out of 79 children, 38 had elbow fractures. The sensitivity and specificity of the posterior fat pad sign diagnosed by US were 97.3% and 90.5%, respectively [37].…”
Section: Us Compared With X-ray In the Diagnosis Of Elbow Fractures (...mentioning
confidence: 97%
“…For supracondylar fractures of the distal humerus (SCFs) US diagnosis in comparison to radiography showed a sensitivity, specificity, NPV, and PPV of 100 %, 93.5 %, 100 %, 95.2 %, respectively [274]. The presence of the posterior/dorsal fat pad sign (dFPS) predicted an elbow fracture with a sensitivity and specificity just under 100 % and a PPV of 90.2 % with an NPV of 97.4 % [275,276]. Similar values of sensitivity and specificity were obtained in the detection of hand and foot bony fractures [277,278] A meta-analysis on occult ankle fractures in children with suspicious symptoms showed that the operating characteristic for US ranged in positive likelihood ratio from 9 to 20 and in negative likelihood ratio from 0.04 to 0.08 [279].…”
Section: Pediatric Traumamentioning
confidence: 99%
“…For supracondylar fractures of the distal humerus (SCFs) US diagnosis in comparison to radiography showed a sensitivity, specificity, NPV, and PPV of 100 %, 93.5 %, 100 %, 95.2 %, respectively 274 . The presence of the posterior/dorsal fat pad sign (dFPS) predicted an elbow fracture with a sensitivity and specificity just under 100 % and a PPV of 90.2 % with an NPV of 97.4 % 275 276 . Similar values of sensitivity and specificity were obtained in the detection of hand and foot bony fractures 277 278…”
Section: Pediatric Applicationsmentioning
confidence: 99%
“…A positive dorsal fat pad sign is seen as a correlate on radiography. Ultrasound has a sensitivity of 97-100 % and a specificity of 90 % here [21,22]. If a joint effusion is detected, radiography is indicated for fracture classification [16,17].…”
mentioning
confidence: 99%